Enhanced visible light photocatalytic degradation of dyes in aqueous solution activated by HKUST-1: performance and mechanism. Issue 61 (7th October 2020) - Zhang, Jianyu; Su, Chunli; Xie, Xianjun; Liu, Peng; Huq, Md. Enamul
Abstract : HKUST-1 is a copper-based metal–organic framework (MOF). The HKUST-1/PMS/Vis system can effectively degrade RhB and MB but accomplish poor removal of AO7 and MR, which is attributed to the repulsion between surface charges. Abstract : HKUST-1 is a copper-based metal–organic framework (MOF) and potential photocatalyst, but minimal research has addressed the performance and mechanism of HKUST-1 in the visible light photocatalytic degradation of dyes. In the present work, HKUST-1 was applied as a photocatalyst to activate peroxomonosulfate (PMS) under visible light (Vis) for dye removal in aqueous solution. The results showed that the removal efficiency of two cationic dyes [rhodamine B (RhB) and methylene blue (MB)] was greater than 95% within 120 min. Free radicals such as SO4 − ˙, ·OH were present in the degradation process, with SO4 − ˙ playing a dominant role. Zeta potential, X-ray photoelectron spectroscopy, and photoluminescence spectroscopy data were used to investigate the degradation mechanism. In the degradation process, surface charge attraction between HKUST-1 and cationic dyes promotes removal efficiency, with the degradation efficiency of cationic dyes (MB and RhB) more than 50% higher than for anionic dyes [acid orange 7 (AO7 ) and methyl red (MR)]. On the other hand, HKUST-1 has been proved to activate PMS by conducting photoelectrons, which accelerated the degradation of dyes. Compared with the reaction conditions of PMS/Vis, when the HKUST-1 was present (HKUST-1/PMS/Vis), the degradation rates of MB and RhB increased by 62.7 and 63.2%, respectively.